DESIGN OF WEB-BASED GALLERY B9 BOOKING SYSTEM AS A MEDIA SERVICE IN DEPARTMENT OF FINE ARTS FACULTY OF LANGUAGE AND ARTS STATE UNIVERSITY OF SEMARANG - Athian, Muhammad Rahman; Murtiyoso, Onang (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2021)
Gallery B9 is one of the facilities in the Department of Fine Arts in supporting the improvement of learning activities at the Department of Fine Arts, FBS, UNNES which is expected to have a Web-based gallery space lending system as a service that is open to anyone who wants to take advantage of the B9 gallery. Aim of this study is 1) to create a web-based booking system as a service media at Studio and Gallery B9 Department of Fine Arts, Semarang State University. 2) to implementing a trial-based studio and gallery lending system as a supporting facility for students of the Department of Fine Arts, Semarang State University. Methodology that used is SDLC, which is used as an appraiser on the website . After using a questionnaire for 22 students. The results obtained that the website -based lending system has good communication effectiveness, this is evident from the results of the questionnaire showing 86% communication efficiency. The problem of the model and visual appearance is vital as a representation of the Department and University, it is considered to have an aesthetic level that is 89% efficient and easy to use. The features on the website are also interesting so they can show 89% results. After testing the loan, 82% said they were satisfied using this feature. The average input provided is giving a checklist about the facilities that are owned in each studio